Three new species of Aricidea (Acmira) (Annelida: Paraonidae) from the Continental Shelf of Eastern Brazil, Southwestern Atlantic - Barroso, R.; Paiva, P.c.; Ranauro, N. (Zootaxa, 2020)
Three new species of the Paraonidae genus Aricidea (Acmira) are described from the Southwestern Atlantic, East Brazilian Continental Shelf (from depths between 11 and 44 m) in the Espírito Santo Basin. The species Aricidea (Acmira) filamentosa sp. nov., Aricidea (Acmira) pearti sp. nov. and Aricidea (Acmira) bbkingi sp. nov. are clearly different from all known species in the genus through its chaetal morphology, number of branchiate chaetigers and shape of antenna. These three species were found in only a few sampling stations, geographically and bathymetrically restricted within a much wider sampled area.